Valoración del Índice de Calidad del Agua Cruda (ICA), del Índice de Riesgo de la Calidad del Agua para Consumo Humano (IRCA), del Índice de Tratamiento (IT), del Índice de Continuidad (IC) y del Índice de Riesgo Municipal por Abastecimiento de Agua para Consumo Humano por Prestador (Irabapp), para el periodo 2010 - 2011, de sistemas de tratamiento de agua potable - Romero Rojas, Jairo Alberto; Ibarra Prado, Nathaly Alejandra (Universidad Escuela Colombiana de Ingeniería Julio Garavito, 2013)
En este artículo se presentan los resultados de la evaluación del Índice de Calidad del Agua Cruda (ICA), Índice de Riesgo de la Calidad del Agua para Consumo Humano (IRCA), Índice de Tratamiento (IT), Índice de Continuidad (IC) e Índice de Riesgo por Abastecimiento de Agua para Consumo Humano por Prestador (Irabapp), para abastecimientos de agua potable municipal, en el periodo 2010 - 2011 (1)

In the area of water quality control, the measurement and the numerical expression of its quality are factors of great importance. A method of continuous quantification of water quality is by means of indexes. According with the Colombian legislation there are different indexes for potable water control. This article provides the results of the evaluation of index of Water Quality Index (WQI), Human Consume Water Risk Index (IRCA, in Spanish), Treatment Index (TI), Continuity Index (IC) and Human Consume Water Supply Risk Index by the water supplier (IRABApp, in Spanish).
Valuation of raw water quality index (WQI), of risk index of water quality for water supply (IRCA), of treatment index (IT), of continuity index (IC), and of water supply for human consumption risk for supplier (IRABApp), for the period 2010 – 2011, of potable water supply systems
Keywords: Calidad del agua - Mediciones; Water quality - Measurement; Índices; Indexes; Agua potable - Normas; Drinking water - Standards; Calidad del agua; Abastecimiento de agua; Agua potable; Índices de calidad del agua; Water quality; Water supply; Drinking water; Water quality indexes